Surgical Correction Of Ectopic Scrotum, Rotational Flap Reconstruction, Multicenter Study - Mohamad, Abdelhalem Shawkat; Abdelhakeem, Omar Nagy; Sabra, Tarek Abdelazeem (Journal of Neonatal Surgery, 2025)
Background; Ectopic scrotum is a rare congenital anomaly. It is the presence of the normal hemiscrotum or a scrotal tissue away from its normal location. The aim of this study is to assess the outcome of surgical correction of ectopic scrotum in children and adult. Patients and methods: Data was collected retrospectively for 15 cases of ectopic scrotum from a multicenter pediatric surgery unit at Minia, A suit and Cairo University. Results: From 15 patients, ten (66.7%) were femoral, two (13.3%) cases were suprainguinal, two (13.3%) cases were infrainguinal and one case was below and lateral to penni. Regarding outcome of surgery; surgical and cosmetic outcome was good and succeed in 93.3% of cases and only one case (6.7%) failed, all adults was succeed and the only one case failed was child. Length of hospital stay after surgery was ranged from 1-3 days with mean of 1.3±0.7 days. Regarding the morning erection was positive in all cases. Conclusion: Single stage rotational flap reconstructing is feasible and safe technique and could achieve good cosmetic and surgical outcome